Analisis Perbandingan Karakteristik Petani Kopi dan Non Petani Kopi dalam Mengurangi Kemiskinan Pada Masyarakat di Provinsi Aceh - Ramadhani Aini Fitri; Fajri Jakfar; Rahmaddiansyah Rahmaddiansyah (Fakultas Pertanian, Universitas Syiah Kuala, 2021)
Planting Aceh is one of the provinces that contributes to coffee production in Indonesia. Aceh Province is one of the plantation commodities that has the potential to increase the pace of the regional economy. However, Aceh is one of the provinces that are classified as poor in Indonesia, in 2018 the number of poor people was 809.76 thousand. This study aims to analyze the characteristics of coffee farmers and non-coffee farmers who are different and analyze the impact of coffee farmers' production in reducing poverty and how the impact of coffee production on reducing poverty in Aceh Province. The type of data used is secondary data from SUSENAS BPS in 2018 and 2019. The analytical method used is descriptive analysis and probit regression. The results of the study are that in 2019 the characteristics that were significantly different between coffee farmers and non-coffee farmers Then the impact of the coffee farmer profession in reducing poverty levels in Aceh Province was seen that the results obtained by non-coffee farmers had more differences in total assets and expenses compared to coffee farmer.